Polystyrene nanoparticles activate ion transport in human airway epithelial cells - RADOMSKI, MAREK; MCCARTHY, JOSEPH (My University, 2011)
Background: Over the last decade, nanotechnology has provided researchers with new nanometer materials, such as nanoparticles, which have the potential to provide new therapies for many lung diseases. In this study, we investigated the acute effects of polystyrene nanoparticles on epithelial ion channel function. Methods: Human submucosal Calu-3 cells that express cystic fibrosis transmembrane conductance regulator (CFTR) and baby hamster kidney cells engineered to express the wild-type CFTR gene were used to investigate the actions of negatively charged 20 nm polystyrene nanoparticles on short-circuit current in Calu-3 cells by Ussing chamber and single CFTR Clchannels alone and in the presence of known CFTR channel activators by using baby hamster kidney cell patches. Results: Polystyrene nanoparticles caused sustained, repeatable, and concentration-dependent increases in short-circuit current. In turn, these short-circuit current responses were found to be biphasic in nature, ie, an initial peak followed by a plateau. EC50 values for peak and plateau short-circuit current responses were 1457 and 315.5 ng/mL, respectively. Short-circuit current was inhibited by diphenylamine-2-carboxylate, a CFTR Cl- channel blocker. Polystyrene nanoparticles activated basolateral K+ channels and affected Cl- and HCO3 - secretion. The mechanism of short-circuit current activation by polystyrene nanoparticles was found to be largely dependent on calcium-dependent and cyclic nucleotide-dependent phosphorylation of CFTR Cl- channels. Recordings from isolated inside-out patches using baby hamster kidney cells confirmed the direct activation of CFTR Cl- channels by the nanoparticles. Conclusion: This is the first study to identify the activation of ion channels in airway cells after exposure to polystyrene-based nanomaterials. Thus, polystyrene nanoparticles cannot be considered as a simple neutral vehicle for drug delivery for the treatment of lung diseases, due to the fact that they may have the ability to affect epithelial cell function and physiological processes on their own.
PUBLISHED
Keywords: Nanotechnology; Pulmonary disorders; Nanoscience & Materials